2011
DOI: 10.1093/bja/aeq364
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation through a small-bore catheter: optimizing expiratory ventilation assistance

Abstract: In laboratory tests, the DE 5 is an optimized ventilation ejector suitable for applying expiratory ventilation assistance. Further research may confirm the clinical applicability as a portable emergency ventilator for use with small-bore catheters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 17 publications
(14 reference statements)
1
23
0
Order By: Relevance
“…Several issues need to be discussed to understand these controversial findings: the measured tracheal and spirometric pressures were not suggestive of either baro‐ or volutrauma, and correlated poorly with the histopathological findings and impairment of gas exchange. Highly negative suction pressures occurred during assisted expiration, but were in line with prior reports , and comparable with levels that are induced during bronchoscopy and endobronchial suctioning . With respect to the discrepancies between pressure monitoring and the clinical pattern, we cannot exclude the possibility that the spirometric devices used were not capable of adequately measuring the acute changes during SLV.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Several issues need to be discussed to understand these controversial findings: the measured tracheal and spirometric pressures were not suggestive of either baro‐ or volutrauma, and correlated poorly with the histopathological findings and impairment of gas exchange. Highly negative suction pressures occurred during assisted expiration, but were in line with prior reports , and comparable with levels that are induced during bronchoscopy and endobronchial suctioning . With respect to the discrepancies between pressure monitoring and the clinical pattern, we cannot exclude the possibility that the spirometric devices used were not capable of adequately measuring the acute changes during SLV.…”
Section: Discussionsupporting
confidence: 84%
“…This limits the effectiveness of oxygenation and carbon dioxide elimination, and may cause air‐trapping, leading to severe baro‐ or volutrauma . To enable sufficient percutaneous small‐lumen ventilation (SLV) after needle tracheotomy, novel manual devices have recently been developed, that make use of the Bernoulli principle to generate a sub‐atmospheric pressure that facilitates and assists expiration . Bench testing has demonstrated the generation of adequate respiratory minute volumes when lungs are ventilated via a 2‐mm internal diameter transtracheal cannula .…”
Section: Introductionmentioning
confidence: 99%
“…Eger and Dunlap have suggested that expiration could be facilitated by applying suction to increase the achievable minute volume through a narrow-bore cannula and lower the risk of air trapping [55,56]. An ejector applying expiratory ventilation assistance achieved a minute volume of 6.1-7.5 l.min )1 through a 2-mm ID transtracheal cannula when used in vitro at a driving flow of 15 l.min )1 [57]: a portable, emergency ventilator applying this technique is now commercially available (Ventrain; Dolphys Medical BV, Eindhoven, The Netherlands; http://www.ventrain.eu/public/ files/ventrain%20brochure%20EN.pdf). Clinical studies need to be conducted to determine its efficacy in a CICO situation.…”
Section: Narrow-bore Cricothyroidotomymentioning
confidence: 99%
“…Problems inherent to this method of translaryngeal and transtracheal oxygenation are the often insufficient expiration and/or ventilation, followed by hypercarbia and the potential for barotrauma and a disruption in hemodynamics, particularly in the presence of closure of the supraglottic airway. The elimination of CO 2 can be improved by systems which ensure expiration or an outflow of expirated air even with a fully obstructed upper airway [59][60][61][62]. …”
Section: Translaryngeal and Transtracheal Oxygenation And Ventilationmentioning
confidence: 99%